Collaboration risk management in IT-enabled asymmetric partnerships: Evidence from telestroke networks. Issue 4 (December 2018) - Singh, Rajendra; Baird, Aaron; Mathiassen, Lars
Abstract: Information technology (IT)-enabled partnerships can unlock previously unattainable value propositions between organizations that have resource, capability, and other asymmetries by allowing larger organizations access to niche and local resources while providing smaller organizations access to enhanced resources and capabilities. However, recent studies have shown that many IT-enabled asymmetric partnerships often fail because the organizations do not effectively manage the involved collaboration risks. Most organizations focus on the strategic aspect of whether partners behave cooperatively or competitively, while paying scant attention to the operational aspect of bringing together partner contributions through coordination. To examine this problem, we report on a case study of two hub-spoke networks that used telemedicine to facilitate expertise sharing and decision making about stroke treatment at emergency departments in rural hospitals (spokes) based on information exchanges with remote neurologists at academic medical centers (hubs). As a result, we contribute to the inter-organizational information systems literature by explaining how organizations in IT-enabled asymmetric partnerships manage collaboration risks. We demonstrate how partners in such relationships perceive and approach strategic cooperation and operational coordination risks differently. We also explain how collaboration interactions change over time as the partners manage risks based on needs and resource endowments. Drawing on these findings, we provide guidance to organizations on how to manage sustainable IT-enabled asymmetric partnerships in general, and telestroke networks in particular. Highlights: Focus on management of cooperation (strategic) and coordination (operational) risks in IT-enabled asymmetric partnerships. Analyze the risks in 32 dyads, each representing an academic medical center (hub) and a rural hospital (spoke), across two telestroke networks. Reveal the evolution of collaboration interactions within and between hospitals collaborating through telestroke.